Bibliometric Analysis of Conversational Marketing - Loso Judijanto (Westscience Press, 2026)
This study aims to map and analyze the intellectual structure, thematic evolution, and research trends in conversational marketing using a bibliometric approach. Data were collected from the Scopus database using relevant keywords related to conversational marketing, artificial intelligence, chatbots, and digital interaction. The analysis was conducted using bibliometric techniques, including co-occurrence, co-authorship, and thematic mapping, supported by visualization tools such as VOSviewer. The findings reveal that conversational marketing has developed as an interdisciplinary field, with artificial intelligence serving as the central foundation linking marketing, communication, and user experience. The results also indicate a clear evolution of research themes, from early communication-focused studies to the integration of machine learning and natural language processing, and more recently toward advanced conversational AI, personalization, and customer experience. Furthermore, the study identifies emerging topics such as anthropomorphism, large language models, and conversational commerce as key directions for future research. This study contributes by providing a comprehensive overview of the field and highlighting potential avenues for further theoretical and empirical development in conversational marketing.